Organizational communication on Twitter: Differences between non-profit and for-profit organizations in the context of climate change - Kim Holmberg; Iina Hellsten (Springer, 2022)
Twitter as a socio-technical platform provides organizations with new ways to reach their stakeholders. In this paper, we compare the use of Twitter specific affordances – such as hashtags, mentions of usernames and sharing of URLs along the tweets in a sample of 1520 tweets sent by 16 profit organizations, and 1042 tweets sent by 18 non-profit organizations in the context of climate change debate. We also compare the use of Twitter for information sharing, engaging in the community and calls-for-action (Lovejoy & Saxton 2012) between the organizations. Our results show that non-profit organizations used Twitter more for engaging in community than profit organizations whose tweets were almost completely (96%) about information sharing. Non-profit organizations shared more hashtags than profit-organizations, in particular hashtags related to campaigns and events. We can conclude that the two types of organizations used Twitter specific affordances differently to reach their targeted audiences.
Crossmedia-Kommunikation in kulturbedingten Handlungsräumen